Geochemistry of Epigenesis - Perel'man, Aleksandr I. (Springer eBooks, 2017)
In its classical sense "epigenesis" refers to all geological processes originating at or near the surface of the earth. It thus embraces all those phenomena which we associate with the land scape; Perel'man has already written extensively on this subject. The landscape, in the physical sense, is controlled by the interac tion of exogenic and endogenic agencies-on the one hand, the atmo sphere, the wind, the rain, and other components of the weather, the forces of running water and the planetary controls of gravitational and tidal nature; and on the other hand the materials of the earth's crust, from sediments to metamorphic rocks and igneous materials from deep endogenic sources. In practical terms the epigene region involves the products of weathering, the soils, the transported material, the colluvium of hillsides, and the alluvium of stream valleys. It involves those landforms that are products of the erosional sculpturing of the landscape, as well as those that result from accumulation, such as glacial moraines and desert sand dunes. The science of geomor phology is gradually beginning to evolve from a passive cataloging of scenery and its deduced causes (in the Davisian sense) into a vigorous study of dynamic processes. These are partly geophysical, in the sense of hydraulics and mechanical studies, and partly geo chemical.